Anti-BpMP-I: produção e caracterização de anticorpos policlonais IgY e IgG anti-metaloprotease - Souza, Dayane Lorena Naves de (2015)
BpMP-I is a non-hemorrhagic metalloprotease isolated and fibrinogenolytic the venom of B. pauloensis. In the present work , we investigated the cross-reactivity of polyclonal anti-BPMP-I (IgG and IgY) isolated from the serum of mice (Balb-C) and chicken egg yolk (White Leghorn). The antibodies were used to detect potential antigens in venoms for enrichment of antivenom. Subsequently, the anti-BPMP-I antibodies (IgG and IgY) were coupled to affinity columns for isolation of target proteins. Proteins binding to the anti-BPMP-I (IgY and IgG-Sepharose Sepharose) were subjected to 2D electrophoresis analysis and mass spectrometry MALDI TOF / TOF. The BPMP-I antibodies were also used to identify metalloproteinases in secretome primary line of breast cancer (MACL-1). Initially, the results of specific reactivity against BpMPI confirmed the efficacy of immunization and showed a strong cross reactivity between the venom of B. pauloensis, B. jararaca, B. and B. atrox diporus. No cross reactivity was detected in the venom of Crotalus durissus collilineatus and phospholipase A2 (BnSP7), which was used as a negative antigen. The antibodies were effective in inhibiting the azocaseinolítica and hemorrhagic activities BPMP-I and the venom of B. pauloensis respectively, confirming its potential neutralization. Approximately, 20 (specific for IgY) and 23 (specific for IgG) were detected spots on 2D SDS-PAGE, and only 11 spots were sequenced by identifying mainly metalloproteases PIII class and type-C lectin domains. Furthermore, the anti-BPMP-I antibodies were capable of recognizing proteins in the range of 72 kDa present in secretome primary line of breast cancer (MACL-1), probably, MMP-2, a highly expressed metalloprotease in a variety of malignant cells such as breast cancer. Taken together, our results showed that anti-BPMP-I polyclonal antibodies were able to recognize metalloproteases in different venoms and secretome breast cancer cells, suggesting their use as potential candidates for inclusion in antiophidic or treating and diagnosis of cancer.